Caspase-cleaved fragments of cytokeratin 18 in patients with chronic hepatitis B - EREN, FATİH; YILMAZ, YUSUF (ELSEVIER SCIENCE BV, 2010)
Background: During hepatocyte apoptosis, intermediate filament protein cytokeratin 18 is cleaved by caspases at Asp396 which can be specifically detected by the monoclonal antibody M30 (M30-antigen). In this study, we sought to determine whether serum M30-antigen levels can serve as a useful biomarker of liver injury in the clinical spectrum of HBV infection. Methods: Serum M30-antigen levels were measured in inactive HBV carriers (n=54), patients with HBeAg-negative chronic hepatitis B (CHB. n=47), patients with HBeAg-positive CHB (n=42) and healthy controls (n=29). All subjects were treatment-nave. Results: There were significant differences in serum M30-antigen levels across the study groups (P<0.001; Kruskal-Wallis test). Post hoc analyses revealed that M30-antigen levels did not differ significantly between inactive HBV carriers (median 109.6 U/L) and healthy controls (median 106.1 U/L). However, both patients with HBeAg-negative (CHB, median 182.9 U/L, P<0.001) and HBeAg-positive CHB (median 158.3 UP., P<0.001) had significantly higher levels of M30-antigen compared with inactive HBV carriers. Conclusions: Hepatocyte apoptotic activity - as reflected by serum M30-antigen levels - is increased in chronic active hepatitis B, but is not associated with the HBeAg status. In contrast, apoptosis does not appear to be a prominent feature of inactive HBV carriers. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cytokeratin 18; Apoptosis; Chronic hepatitis B; Inactive carriers; EXTRACELLULAR CYTOKERATIN-18; DIAGNOSTIC-TESTS; SOLUBLE FORMS; LIVER-INJURY; APOPTOSIS; INFECTION